2018
DOI: 10.1002/hbm.24407
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between socioeconomic status and white matter microstructure in pre‐reading children: A longitudinal investigation

Abstract: Reading is a learned skill crucial for educational attainment. Children from families of lower socioeconomic status (SES) tend to have poorer reading performance and this gap widens across years of schooling. Reading relies on the orchestration of multiple neural systems integrated via specific white-matter pathways, but there is limited understanding about whether these pathways relate differentially to reading performance depending on SES background. Kindergarten white-matter FA and second-grade reading outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 144 publications
(223 reference statements)
3
54
0
3
Order By: Relevance
“…For example, participants could use orthographic strategies and visual imagery while searching for morphologically-related words. In this case, the effects observed in the ventral tracts may reflect their well-known involvement in orthographic processing (Banfi et al, 2019;Horowitz-Kraus et al, 2014;Huber et al, 2018;Ozernov-Palchik et al, 2019;Vandermosten et al, 2012;Yeatman et al, 2012a). Although the current data do no not allow to preclude this alternative explanation of the results, it seems less plausible given that morpheme-based fluency was not correlated with reading ability.…”
Section: Limitationsmentioning
confidence: 52%
See 2 more Smart Citations
“…For example, participants could use orthographic strategies and visual imagery while searching for morphologically-related words. In this case, the effects observed in the ventral tracts may reflect their well-known involvement in orthographic processing (Banfi et al, 2019;Horowitz-Kraus et al, 2014;Huber et al, 2018;Ozernov-Palchik et al, 2019;Vandermosten et al, 2012;Yeatman et al, 2012a). Although the current data do no not allow to preclude this alternative explanation of the results, it seems less plausible given that morpheme-based fluency was not correlated with reading ability.…”
Section: Limitationsmentioning
confidence: 52%
“…In the current study, participants used auditorily presented morphological information as a cue for lexical search and oral word production. Although this task did not explicitly involve reading, performance was correlated with the bilateral IFOF and ILF, suggesting that their role in morphememediated lexical access goes beyond their well-established involvement in orthographic processing (Horowitz-Kraus et al, 2014;Ozernov-Palchik et al, 2019;Vandermosten et al, 2012;Welcome and Joanisse, 2014;Yeatman et al, 2012a). Importantly, the associations between morpheme-based fluency and the ventral tracts remained significant when performance in standard verbal fluency tasks was accounted for, suggesting that the observed effects are somewhat specific to the morphological component of the task.…”
Section: Morpheme-based Fluency Is Associated With Ventral and Dorsalmentioning
confidence: 94%
See 1 more Smart Citation
“…Certain environmental and family-related factors have also been strongly linked with reading development, particularly those related to socioeconomic status [38][39][40] . Research has repeatedly shown the critical impact of socioeconomic status on language and reading development 38,41,42 . From early childhood, significant disparities in vocabulary knowledge have been observed when comparing children from high versus low socioeconomic backgrounds 43,44 .…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Regional white matter DTI has been correlated to language ability and pre-reading skills in younger ''pre-readers'' (Saygin et al, 2013;Vandermosten et al, 2015;Wang et al, 2017;Dodson et al, 2018;Vanderauwera et al, 2018;Walton et al, 2018;Ozernov-Palchik et al, 2019;Hutton et al, 2020), and even in infants with a family history of developmental dyslexia (Langer et al, 2017). Longitudinal DTI has shown that both baseline values and changes of diffusion parameters between scans predict future reading ability in healthy controls (Hoeft et al, 2011;Yeatman et al, 2012;Myers et al, 2014;Gullick and Booth, 2015;Takeuchi et al, 2016;Vanderauwera et al, 2017;Borchers et al, 2019;Bruckert et al, 2019;Lebel et al, 2019) and in neurodevelopmental disorders such as fetal alcohol spectrum disorders (Treit et al, 2013).…”
Section: Introductionmentioning
confidence: 99%